A method for testing water resistance of coated diaphragm
By soaking and drying the diaphragm sample in the fixture, measuring its mass and heat shrinkage, and evaluating the water resistance of the diaphragm with peeling force, the problem of difficulty in evaluating the water resistance of the diaphragm coating layer in the prior art is solved, and high accuracy is achieved test and feasibility assessment of secondary coating.
Patent Information
- Application Number
- CN202210259402.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-03-15
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2042-03-15
AI Technical Summary
The prior art is difficult to effectively evaluate the water resistance of the diaphragm coating layer, resulting in poor coating and poor secondary coating, resulting in scrapping.
By cutting the separator sample and soaking and drying in a fixture with holes, the mass and heat shrinkage are measured, the water resistance is calculated, and the water resistance of the coated separator is evaluated in combination with peeling force to avoid wrinkles on the roll and improve measurements accuracy.
The accuracy and rapid evaluation of the diaphragm water resistance test is achieved, the scrap situation caused by poor secondary coating is avoided, and the feasibility of secondary processing of the coating is improved.
Smart Images

Figure CN114755155B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of diaphragm production, and in particular to a method for testing the water resistance of a coated diaphragm. Background Art
[0002] As an important component of lithium batteries, the diaphragm plays the role of blocking direct contact between the positive and negative electrodes, while allowing lithium ions to pass freely and blocking the shuttle of electrons, which is of great help to the safety of the battery. Since the base film of the diaphragm itself has poor heat resistance, a heat-resistant layer is often coated on one or both sides of the base film surface to improve the heat resistance of the base film. Since the heat-resistant layer is generally composed of heat-resistant materials such as alumina and boehmite, there is no bonding effect between it and the positive and negative electrodes. In order to improve the hardness of the battery, a layer of adhesive layer with bonding to the positive and negative electrodes is generally coated on the surface of the heat-resistant layer. This adhesive layer is often water-based PMMA, water-based PVDF, etc. The water resistance of the heat-resistant layer directly determines the coating quality of the adhesive layer. When the water resistance is poor, poor coating will occur, such as coating powdering, poor thermal shrinkage of the coating, etc. Therefore, it is necessary to test the water resistance of the heat-resistant layer to evaluate whether the adhesive layer can be coated on the heat-resistant layer.
[0003] Patent No. CN201810779051.7 invented a method for detecting the water resistance of powder spray coatings. The method accelerates the discoloration of the coating by changing the environment, and thus evaluates the water resistance of the coating by the color difference between closed and non-closed types. Since the diaphragm coating material does not change color with the environment, the above method is not suitable for evaluating the water resistance of the diaphragm coating layer. Summary of the invention
[0004] In view of the deficiencies in the prior art, the present invention provides a method for testing the water resistance of a coated diaphragm, which can improve the accuracy of the water resistance test of the coated diaphragm, can quickly evaluate the feasibility of secondary processing of the coating, and avoid scrapping due to poor secondary coating.
[0005] To achieve the above purpose, the present invention adopts the following technical solutions:
[0006] A method for testing the water resistance of a coated diaphragm comprises the following steps:
[0007] S1, cutting the diaphragm samples and the corresponding base film samples of the same size, respectively measuring the mass M1 of a single diaphragm sample, the mass M0 of a single base film sample, the peeling force F1 of the diaphragm sample, the heat shrinkage rate X1 of the diaphragm sample in the MD direction, and the heat shrinkage rate Y1 of the diaphragm sample in the TD direction;
[0008] S2. Flatten the membrane sample and place it in a fixture with holes, then immerse the fixture in deionized water for a certain period of time, and make the deionized water cover the membrane sample;
[0009] S3, taking out the fixture and putting it into an oven to bake the diaphragm sample;
[0010] S4. Take out the dried membrane sample from the fixture, and measure the mass M2 of the dried single membrane sample, the peeling force F2 of the membrane sample, the heat shrinkage X2 of the membrane sample in the MD direction, and the heat shrinkage Y2 of the membrane sample in the TD direction.
[0011] S5. Calculate the water resistance related values respectively: a=(1-(M1-M2) / (M1-M0))*100%, b=(|F2-F1|) / F1*100%, c=(|X1-X2|) / X1*100%, d=(|Y2-Y1|) / Y1*100%;
[0012] S6. Determine the water resistance of the coated diaphragm according to the magnitude of the water resistance-related numerical value.
[0013] By placing the diaphragm sample in the fixture during the soaking and drying process, wrinkling of the diaphragm surface is avoided, thereby improving the accuracy of the measurement result.
[0014] As a preferred solution, in step S1, when testing the thermal shrinkage rate of the diaphragm sample, the diaphragm sample is baked at 130° C. for 1 hour.
[0015] As a preferred solution, in step S2, the fixture is controlled to rotate at a certain speed during the immersion process. By rotating the fixture at a certain speed during the immersion process, the diaphragm sample is more fully in contact with the deionized water, which can effectively reduce the test error.
[0016] As a preferred solution, in step S2, during the immersion process, the fixture is controlled to rotate at a speed of 100±4 rpm / min, and the immersion time is 30 minutes.
[0017] As a preferred solution, when drying the sample to be tested, the fixture is placed in an oven at 60° C. for 4 hours.
[0018] As a preferred solution, in step S3, the size of the diaphragm sample and the corresponding basement membrane sample are both 10 cm*10 cm.
[0019] As a preferred solution, the fixture is made of two stainless steel plates, a groove for placing the diaphragm sample is provided between the two stainless steel plates, a hole penetrates the stainless steel plate and is connected to the groove, and the depth of the groove is greater than the thickness of the diaphragm sample and less than twice the thickness of the diaphragm sample. By setting a suitable groove depth, the diaphragm roll surface can be prevented from wrinkling while ensuring the diaphragm is flattened, thereby improving the measurement accuracy.
[0020] Compared with the prior art, the present invention has obvious advantages and beneficial effects. Specifically, by placing the diaphragm sample in a clamp, the diaphragm sample can be well spread in the water without curling or wrinkling. At the same time, the immersed diaphragm is dried without external force, and the water resistance of the heat-resistant layer coated with the diaphragm is evaluated by combining the diaphragm characteristic indicators of peeling force and thermal shrinkage rate, so that the measurement result is more accurate, more comprehensive and reliable, and the feasibility of secondary processing of the coating can be quickly evaluated to avoid the situation where scrapping is caused by poor secondary coating. By controlling the constant speed rotation of the clamp during the immersion process, the diaphragm sample is more fully immersed in deionized water, so that the test result is more accurate.
[0021] In order to more clearly explain the structural features, technical means and specific purposes and functions achieved by the present invention, the present invention is further described in detail below in conjunction with the accompanying drawings and specific embodiments: BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 It is a schematic diagram of the assembly structure of the testing device according to an embodiment of the present invention;
[0023] Figure 2 Schematic diagram of the structure of a stainless steel plate according to an embodiment of the present invention;
[0024] Figure 3 It is a schematic diagram of the cross-sectional structure of a clamp according to an embodiment of the present invention.
[0025] Description of the accompanying drawings:
[0026] 10. Soaking box 11. Sealed door 12. Handle
[0027] 13. Water inlet 14. Water outlet 15. Valve
[0028] 20. Test fixture 21. Stainless steel plate 22. Groove
[0029] 23. Hanging hole 24. Hole 25. Magnet
[0030] 30. Motor 31. Rotating shaft 32. Hook
[0031] 40. Controller 41. Motor switch 42. Speed display screen
[0032] 43. Up button 44. Down button 45. Start / Pause button
[0033] 50. Diaphragm samples DETAILED DESCRIPTION
[0034] In the description of the present invention, it should be noted that the terms "center", "up", "down", "left", "right", "vertical", "horizontal", "inside" and "outside" etc. indicate directions or positional relationships based on the directions or positional relationships shown in the accompanying drawings. They are only for the convenience of describing the invention and simplifying the description, and do not indicate or imply that the positions or elements referred to must have specific directions, be constructed and operated in specific directions. Therefore, they should not be understood as limitations on the present invention.
[0035] A method for testing the water resistance of a coated diaphragm of the present invention comprises the following steps:
[0036] S1, cutting the diaphragm sample and the corresponding base film sample with a size of 10cm*10cm, respectively measuring the mass M1 of a single diaphragm sample, the mass M0 of a single base film sample, the peeling force F1 of the diaphragm sample, the heat shrinkage rate X1 of the diaphragm sample in the MD direction, and the heat shrinkage rate Y1 of the diaphragm sample in the TD direction; wherein, when testing the heat shrinkage rate of the diaphragm sample, the diaphragm sample is baked at 130°C for 1 hour;
[0037] S2. Flatten the membrane sample and place it in a fixture with holes, then immerse the fixture in deionized water for a certain period of time, and make the deionized water cover the membrane sample; during the immersion process, control the fixture to rotate at a speed of 100±4rpm / min, and the immersion time is 30 minutes; by rotating the fixture at a certain speed during the immersion process, the membrane sample can be more fully in contact with the deionized water, which can effectively reduce the test error.
[0038] S3, take out the fixture and put it into a 60°C oven for 4 hours to dry the diaphragm sample;
[0039] S4, taking out the dried membrane sample from the fixture, and measuring the mass M2 of the dried single membrane sample, the peeling force F2 of the membrane sample, the heat shrinkage rate X2 of the membrane sample in the MD direction, and the heat shrinkage rate Y2 of the membrane sample in the TD direction;
[0040] S5. Calculate the water resistance related values, a=(1-(M1-M2) / (M1-M0))*100%, b=(|F2-F1|) / F1*100%, c=(|X1-X2|) / X1*100%, d=(|Y2-Y1|) / Y1*100%;
[0041] S6. The water resistance of the coated diaphragm is judged according to the magnitude of the water resistance-related numerical values. In the present invention, when a≥98%, b≤5%, c≤5%, and d≤5%, it means that the water resistance of the heat-resistant layer of the diaphragm meets the requirements.
[0042] By placing the diaphragm sample in the fixture during the soaking and drying process, wrinkling of the diaphragm surface is avoided, thereby improving the accuracy of the measurement result.
[0043] like Figure 1-3 As shown, the testing device of the present invention comprises an immersion box 10 and a fixture 20. The upper end of the immersion box 10 is provided with a motor 30 and a controller 40 for controlling the speed of the motor 30. The controller 40 is provided with a motor switch 41, a speed adjustment button, a start / pause button 45 and a speed display screen 42. The speed adjustment button comprises an up-adjustment button 43 and a down-adjustment button 44. The motor 30 is provided with a rotating shaft 31 extending downward into the immersion box 10. The lower end of the rotating shaft 31 is provided with a hook 32. The fixture 20 is provided with a hanging hole 23 corresponding to the hook 32. The fixture 20 comprises two openable stainless steel plates 21. A groove 22 for placing a diaphragm sample 50 is provided between the two stainless steel plates 21. The stainless steel plate 21 is provided with a plurality of holes 24 connected to the groove 22. The depth of the groove 22 is greater than the thickness of the diaphragm sample 50 and less than twice the thickness of the diaphragm sample 50. By setting the clamp 20, the diaphragm sample 50 can be placed in the clamp 20, so that the diaphragm sample 50 can be well spread without curling and wrinkling during the immersion process; by setting the motor 30, the clamp 20 can be controlled to rotate at a fixed speed during the immersion process, so that the immersion is more complete, thereby improving the accuracy of the test results. The distance between the hook 32 and the inner bottom wall of the immersion box 10 is greater than the distance between the farthest two ends of the clamp 20, so that the clamp 20 can be suspended and rotated in the immersion box 10 during the test, avoiding bumps and causing the coating to fall off, thereby improving the accuracy of the test results. A sealed door 11 for placing and removing the clamp 20 is provided on one side of the immersion box 10, and a handle 12 is provided on the sealed door 11. The sealed door 11 is arranged in the middle of the side wall of the immersion box 10. The upper and lower ends of the immersion box 10 are respectively provided with a water inlet 13 and a water outlet 14, and a valve 15 is provided at the water outlet 14. Magnets 25 are provided at the edges of the opposing surfaces of the two stainless steel plates 21. The magnets 25 at corresponding positions on the two stainless steel plates 21 have opposite magnetic poles, and the two stainless steel plates 21 are connected by the magnets 25. Both stainless steel plates 21 are square, and the hanging hole 23 is provided at a corner of the stainless steel plate 21. The holes 24 on the stainless steel plate 21 are evenly distributed, and the diameter of the holes 24 is 3 to 6 mm.
[0044] The following is further described with specific embodiments:
[0045] Example 1: Take diaphragm A, test the heat shrinkage rate (130℃ / h) and peeling force respectively, the heat shrinkage in MD direction is X1=5.55%, the heat shrinkage in TD direction is Y1=4.24%, the peeling force is F1=63.2N / m, then take 10cm*10cm diaphragm sample A and its corresponding base film, weigh the mass M1=0.0703g, M0=0.0465g; put diaphragm sample A into a stainless steel fixture, and then put the stainless steel fixture into the immersion box , close the water outlet and the sealing door, add deionized water to 2 cm above the hook, set the motor speed to 100 rpm / min, press the start button, soak for 30 minutes, drain the deionized water, take out the stainless steel clamp, put it in a 60℃ oven and bake it for 4 hours, weigh the mass M2 of the diaphragm after soaking, and measure its peel force F2 and thermal shrinkage rate X2 / Y2, M2=0.0701g, F2=62.8N / m, X2=5.61%, Y2=4.34%.
[0046] Example 2: Take the diaphragm B, test the heat shrinkage (130℃ / h) and peeling force respectively, the heat shrinkage in MD direction X1=4.53%, the heat shrinkage in TD direction Y1=3.86%, the peeling force F1=53.5N / m, then take the 10cm*10cm diaphragm sample B and its corresponding base film, weigh the mass M1=0.0686g, M0=0.0452g, put the diaphragm sample B into the stainless steel fixture, and then put the stainless steel fixture into Soak in the box, close the water outlet and seal the door, add deionized water to 2 cm above the hook, set the motor speed to 100 rpm / min, press the start button, soak for 30 minutes, drain the deionized water, take out the stainless steel clamp, put it in a 60℃ oven and bake for 4 hours, weigh the mass M2 of the diaphragm after soaking, and measure its peel force F2 and thermal shrinkage X2 / Y2, M2=0.0682g, F2=53.5N / m, X2=5.04%, Y2=4.33%.
[0047] Example 3: Take the separator C and test the thermal shrinkage (130℃ / h) and peeling force respectively. The heat shrinkage rate in the MD direction is X1=3.23%, the heat shrinkage rate in the TD direction is Y1=2.53%, and the peeling force is F1=86.4N / m. Then take a 10cm*10cm diaphragm sample C and a base film of the corresponding size, and weigh the mass M1=0.0694g, M0=0.0458g. Put the diaphragm sample C into a stainless steel fixture, and then put the stainless steel fixture into the immersion box, close the water outlet and the sealing door, add deionized water to 2cm above the hook, set the motor speed to 100rpm / min, press the start button, soak for 30min, drain the deionized water, take out the stainless steel fixture, put it in a 60℃ oven and bake for 4h, weigh the mass M2 of the diaphragm after immersion, and measure its peeling force F2 and heat shrinkage X2 / Y2, M2=0.0690g, F2=40.3N / m, X2=3.23%, Y2=2.64%.
[0048] Example 4: Take the separator D and test the thermal shrinkage (130℃ / h) and peeling force respectively. The heat shrinkage rate in the MD direction is X1=4.15%, the heat shrinkage rate in the TD direction is Y1=3.55%, and the peeling force is F1=57.5N / m. Then take a 10cm*10cm diaphragm sample D and a base film of the corresponding size, and weigh the mass M1=0.0689g, M0=0.0462g. Put the diaphragm sample D into a stainless steel fixture, and then put the stainless steel fixture into the immersion box, close the water outlet and the sealing door, add deionized water to 2cm above the hook, set the motor speed to 100rpm / min, press the start button, soak for 30min, drain the deionized water, take out the stainless steel fixture, put it in a 60℃ oven and bake for 4h, weigh the mass M2 of the diaphragm after immersion, and measure its peeling force F2 and heat shrinkage X2 / Y2, M2=0.0685g, F2=42.1N / m, X2=5.31%, Y2=4.28%.
[0049] Example 5: Take separator E and test its thermal shrinkage (130°C / h) and peeling force. The heat shrinkage rate in the MD direction is X1=4.54%, the heat shrinkage rate in the TD direction is Y1=3.64%, and the peeling force is F1=70.7N / m. Then take a 10cm*10cm diaphragm sample E and a base film of the corresponding size, weigh their masses M1=0.0702g and M0=0.0456g, put the diaphragm sample E into a stainless steel fixture, and then put the stainless steel fixture into the immersion box, close the water outlet and the sealing door, add deionized water to 2cm above the hook, set the motor speed to 100rpm / min, press the start button, soak for 30min, drain the deionized water, take out the stainless steel fixture, put it in a 60℃ oven and bake for 4h, weigh the diaphragm mass M2 after immersion, and measure the peeling force F2 and heat shrinkage X2 / Y2, M2=0.0598g, F2=46.4N / m, X2=5.78%, Y2=5.46%.
[0050] The water resistance values of the diaphragms of various embodiments were calculated and shown in Table 1:
[0051]
[0052] The water resistance of the diaphragm in each embodiment is judged according to the calculation results in Table 1:
[0053] In Example 1, the performance of the diaphragm A meets the water resistance standard, and the diaphragm A is water resistant;
[0054] In Example 2, the mass loss and peeling force performance of the separator B meet the water resistance standard, but the heat shrinkage performance does not meet the water resistance standard, and the separator B is not water-resistant;
[0055] In Example 3, the mass loss and heat shrinkage performance of the separator C meet the water resistance standard, but the peeling force performance does not meet the water resistance standard, and the separator C is not water-resistant;
[0056] In Example 4, the mass loss of the separator D meets the water resistance standard, but the peeling force and heat shrinkage performance do not meet the water resistance standard, and the separator D is not water-resistant;
[0057] The mass loss, peeling force and heat shrinkage performance of the separator E in Example 5 do not meet the water resistance standard, and the separator E is not water-resistant.
[0058] In order to further verify the effectiveness of this method for testing the water resistance of the diaphragm, the diaphragms A, B, C, D, and E are subjected to secondary processing:
[0059] Take diaphragms A, B, C, D, and E, and test the peel force F1 and heat shrinkage rate (130℃ / h), heat shrinkage rate X1 in MD direction, and heat shrinkage rate Y1 in TD direction of various diaphragms respectively. Then put the diaphragms on the machine for secondary coating. After unwinding, secondary coating, drying, and winding, secondary processed diaphragms A1, B1, C1, D1, and E1 are obtained. Then, the peel force F2, heat shrinkage rate X2 in MD direction, and heat shrinkage rate Y2 in TD direction of the secondary processed diaphragms are tested. Finally, the peel force and heat shrinkage rate of the diaphragms before and after secondary coating are compared.
[0060] The water resistance values of each diaphragm after secondary processing are calculated and shown in Table 2:
[0061]
[0062] As can be seen from Table 2, before and after the secondary processing of diaphragm A, the changes in the diaphragm peeling force and heat shrinkage before and after meet the water resistance standard, and diaphragm A is water-resistant; after the secondary processing of diaphragm B, the peeling force performance meets the water resistance standard, and the heat shrinkage performance does not meet the water resistance standard, and diaphragm B is not water-resistant; after the secondary processing of diaphragm C, the peeling force performance does not meet the water resistance standard, and the heat shrinkage performance meets the water resistance standard, and diaphragm C is not water-resistant; after the secondary processing of diaphragms D and E, the peeling force and heat shrinkage performance do not meet the water resistance standard, and diaphragms D and E are not water-resistant. It can be seen that the secondary processing results of the diaphragms are consistent with the results of the water resistance of the diaphragms tested by the method of the present invention. The present invention can effectively and accurately measure the water resistance of the diaphragm, which is conducive to quickly evaluating the feasibility of secondary processing of the coating.
[0063] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Therefore, any modification, equivalent replacement, improvement, etc. made to the above embodiment based on the technical practice of the present invention still falls within the scope of the technical solution of the present invention.
Claims
1. A method for testing the water resistance of a coated diaphragm, characterized in that: The following steps are involved: S1, cutting the diaphragm samples and the corresponding base film samples of the same size, respectively measuring the mass M1 of a single diaphragm sample, the mass M0 of a single base film sample, the peeling force F1 of the diaphragm sample, the heat shrinkage X1 of the diaphragm sample in the MD direction, and the heat shrinkage Y1 of the diaphragm sample in the TD direction; S2. Flatten the membrane sample and place it in a fixture with holes, then immerse the fixture in deionized water for a certain period of time, and make the deionized water cover the membrane sample; S3, taking out the fixture and putting it into an oven to bake the diaphragm sample; S4, taking out the dried membrane sample from the fixture, and measuring the mass M2 of the dried single membrane sample, the peeling force F2 of the membrane sample, the heat shrinkage rate X2 of the membrane sample in the MD direction, and the heat shrinkage rate Y2 of the membrane sample in the TD direction; S5. Calculate the water resistance related values a, b, c and d respectively, where a=(1-(M1-M2) / (M1-M0))*100%, b=(|F2-F1|) / F1*100%, c=(|X1-X2|) / X1*100%, d=(|Y2-Y1|) / Y1*100%; S6. The water resistance of the coated diaphragm is judged according to the size of the water resistance related values. When a≥98%, b≤5%, c≤5% and d≤5%, it means that the water resistance of the diaphragm meets the requirements.
2. A method for testing water resistance of a coated diaphragm according to claim 1, characterized in that: In step S1, when testing the thermal shrinkage rate of the diaphragm sample, the diaphragm sample is baked at 130° C. for 1 hour.
3. A method for testing water resistance of a coated diaphragm according to claim 1, characterized in that: In step S2, the fixture is controlled to rotate at a certain speed during the immersion process.
4. A method for testing water resistance of a coated diaphragm according to claim 3, characterized in that: In step S2, during the immersion process, the fixture is controlled to rotate at a speed of 100±4 rpm / min, and the immersion time is 30 minutes.
5. A method for testing water resistance of a coated diaphragm according to claim 1, characterized in that: In step S3, when drying the sample to be tested, the fixture is placed in an oven at 60° C. for 4 hours.
6. A method for testing water resistance of a coated diaphragm according to claim 1, characterized in that: In step S3, the size of the diaphragm sample and the corresponding basement membrane sample are both 10 cm*10 cm.
7. A method for testing water resistance of a coated diaphragm according to claim 1, characterized in that: The fixture is made of two stainless steel plates, between which a groove for placing the diaphragm sample is provided, and a hole penetrates the stainless steel plates and is connected to the groove. The depth of the groove is greater than the thickness of the diaphragm sample and less than twice the thickness of the diaphragm sample.
